Development of functional yogurt containing free and encapsulated echium oil, phytosterol and sinapic acid. (15th December 2017) - Comunian, Talita A.; Chaves, Isabela Elias; Thomazini, Marcelo; Moraes, Izabel Cristina Freitas; Ferro-Furtado, Roselayne; de Castro, Inar Alves; Favaro-Trindade, Carmen S.
Highlights: The coencapsulation of echium oil and phytosterols by complex coacervation was possible. The encapsulation process provided oxidative stability to the bioactive compounds. Yogurt added of microcapsules had better oxidative stability than the yogurt control. Abstract: The consumption of omega-3 fatty acids and phytosterol promotes the reduction of cholesterol and triacylglycerol levels. However, such compounds are susceptible to oxidation, which hampers their application. The objective of this work was to coencapsulate echium oil, phytosterols and sinapic acid (crosslinker/antioxidant), and incorporate the obtained microcapsules into yogurt. The microcapsules were evaluated for particle size, accelerated oxidation by Rancimat, and simulation of gastric/intestinal release. The yogurts were assessed for morphology, pH, titratable acidity, color, rheology and sensory analysis. The microcapsules (13–42 μm) promoted protection against oil oxidation (induction time of 54.96 h). The yogurt containing microcapsules, presented a pH range from 3.89 to 4.17 and titratable acidity range from 0.798 to 0.826%, with good sensorial acceptance. It was possible to apply the microcapsules in yogurt, without compromising the rheological properties and physicochemical stability of the product.